Financial Inclusion As A Tool for Citizen Upliftment: Development of A Measurement Model Based on Citizen Perception - Kumar , Dr. S. Shankar; Chandramowleeswaran , Dr. G.; Harish, Dr. K A; Venkatesan, Dr. D; Rani, Dr T Shalini (International Journal of Accounting and Economics Studies, 2025)
Financial inclusion is a key aspect for social inclusion and inclusive growth for citizen upliftment. Effective financial inclusion is important ‎for enhancing the involvement and access to financial services. Inclusive finance is necessary for effective, reliable, and cost-effective ‎payments towards financial services. The current study aims to determine factors and to develop a financial inclusion measurement scale for ‎citizen upliftment. The current study is a descriptive research with data collected from 405 responses by using non-probability convenience ‎sampling. The data was collected using structured questionnaires with a Likert five-point rating scale and Dichotomous questions. The results revealed 6 prominent factors under financial inclusion, which were Awareness, Access and Usage, Challenges, Impact, Causes, and ‎effectiveness of financial inclusion. The multiple regression model yielded an R Square value of 0.695, explaining 69.5% of the variance. ‎This indicates that the Challenges, Impact, and Causes of Financial Exclusion variables have a significant impact on the output variable, which ‎is the Effectiveness of Financial Inclusion. The provision of the Financial Inclusion Measurement Scale satisfies the promise of generalising the ‎study findings to the stakeholders of the country. The established framework offers ideas and methodology to the appropriate government, ‎civil society, and stakeholders, adding to the insights of the financial inclusion projects.